Policies improving the well-being of GIG workers in Malaysia - Khaizie Sazimah Ahmad; Khairunnisa Abd Samad; Nur Hayati Abd Rahman; Siti Nurazira Mohd Daud; Najihah Hanisah Marmaya; Yenni Samri Juliati Nasution; Raseeda Hamzah (ResearchGate, 2024)
Very scarce research has assessed the extent of adverse effects on the well-being of gig workers, particularly in Malaysia. So, the study aims to examine the policies favoring the well-being of gig workers using qualitative methodology of secondary materials examination and semi-structured interviews with policymakers. One of the key findings is that the Malaysian government is very supportive in welcoming the new era of flexibility and freedom of work, such as gig workers. This is particularly relevant to the gig economy, which is characterized by a high degree of uncertainty and variability. The emergent issues significantly call for government and policymakers to design the right policies to enhance gig workers' welfare.